Host-Induced Silencing of Fusarium graminearum Genes Enhances the Resistance of Brachypodium distachyon to Fusarium Head Blight - He, Fuxin; Zhang, Ruiming; Zhao, Jiaxin; Qi, Tuo; Kang, Zhensheng; Guo, Jun (Frontiers in Plant Science, 2019)
Fusarium head blight (FHB) caused by Fusarium pathogens are devastating diseases worldwide. Host-induced gene silencing (HIGS) which involves host expression of double-stranded RNA (dsRNA)-generating constructs directed against genes in the pathogen has been a potential strategy for the ecological sound control of FHB. In this study, we constructed transgenic Brachypodium distachyon lines carrying RNA interference (RNAi) cassettes to target two essential protein kinase genes Fg00677 and Fg08731, and cytochrome P450 lanosterol C14-α-demethylase (CYP51) encoding genes (CYP51A, CYP51B, and CYP51C) of Fusarium graminearum, respectively. Northern blotting confirmed the presence of short interfering RNAs (siRNA) derived from Fg00677, Fg08731, and CYP51 in transgenic B. distachyon plants, and the transcript levels of the corresponding genes were down-regulated in the F. graminearum colonizing B. distachyon spikes. All the corresponding independent, Fg00677-RNAi, Fg08731-RNAi, and CYP51-RNAi transgenic T2 lines exhibited strong resistance to F. graminearum, suggesting that silencing molecules produced by transgenic plants inhibited the corresponding gene function by down-regulating its expression, thereby reducing pathogenicity. Our results indicate that Fg00677 and Fg08731 are effective targets for HIGS and can be applied to construct transgenic HIGS materials to enhance FHB resistance in wheat and other cereal crops.